A single point-mutation within the melanophilin gene causes the lavender plumage colour dilution phenotype in the chicken - Tixier-Boichard Michèle (BMC Genetics, 2008)
Abstract Background The lavender phenotype in the chicken causes the dilution of both black (eumelanin) and red/brown (phaeomelanin) pigments. Defects in three genes involved in intracellular melanosomal transport, previously described in mammals, give rise to similar diluted pigmentation phenotypes as those seen in lavender chickens. Results We have used a candidate-gene approach based on an expectation of homology with mammals to isolate a gene involved in pigmentation in chicken. Comparative sequence analysis of candidate genes in the chicken identified a strong association between a mutation in the MLPH gene and the diluted pigmentation phenotype. This mutation results in the amino acid change R35W, at a site also associated with similar phenotypes in mice, humans and cats. Conclusion This is the first time that an avian species with a mutation in the MLPH gene has been reported.